Pendampingan Strategi Pemasaran UMKM Desa Giripurno Melalui Digital Marketing - Aiman Anas Bobsaid; Erwan Adi Saputro (LPPM Universitas Trunojoyo Madura, 2022)
In the industrial era 4.0, technological development is quite rapid. This results in the world of marketing products from a business. Marketing in this era generally uses the internet or commonly called digital marketing. Digital marketing is the marketing of a service product or goods marketed using the internet can use the advice of available marketplace platforms such as shopee or using social media facilities such as Instagram. The sale of several MSME partners in Giripurno Village on average still requires consumers to come to the seller's house to buy their products. The purpose of this activity is to provide training and assistance related to digital marketing in order to increase the marketing of MSME products in Giripurno Village. This method of community service has several stages, including the training and mentoring stages. The training stage consists of (1) the introduction of packaging and branding; (2) training related to packaging and product brand; and (3) training to create shopee account as a marketplace account. The mentoring stage consists of (1) an understanding process related to publishing products on the partner shopee account and (2) receiving orders and the process of delivering goods through inter-package services.